IMPROVING SELF-CARE INDEPENDENCY OF TYPE 2 DM PATIENTS BASED ON LASALLIAN EDUCATION MODEL - Annastasia Sintia Lamonge; Wahyuny Langelo; Natalia Rakinaung (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
AbstractThe specific objectives of this study were: (1) Analyze the effectiveness of Lasallian health education in order to increased knowledge and attitude. (2) Analyze the effectiveness of Lasallian health education in order to increase the self-care independency of people with type 2 diabetes mellitus (DM). Research design of this study was Pre-Experiment with target population patients with type 2 DM. 12 participants were recruited in the study with purposive sampling technique. Bivariate test results of knowledge and attitudes before and after giving the Lasallian health education showed significant results with ρ-value of 0.016 (p-value <ά 0.05). Research result of self-care independency of type 2 diabetic patients in before and after giving Lasallian health education show significant result with ρ-value of 0.001 (p-value <ά 0:01). Transformation of people behavior or habit by a health education program should have three important determinant, there are cognitive, affective and psychomotor aspects of participants to motivate and increase self-awareness, and adherence of self-care management and improving of quality of life.Keywords: Type 2 DM, Lasallian Health Education, Knowledge, Attitude, Self-care independency.